THE "FETUS" IS A CHILD! ANALYSIS OF THE PASSIVE SUBJECT OF THE CRIME OF ABORTION. - Funes Orellana, Jorge (2024)
Starting from the legal concept of "person" and "child" introduced by international human rights standards, it is shown that the "fetus" is a person and a child.